VD_FINDINFO HC / 2013 / 807 vom 21. November 2013 - VD Tribunal cantonal (2013)
DIVORCE, MODIFICATION DES CIRCONSTANCES, OBLIGATION D'ENTRETIEN, MESURE PROVISIONNELLE | 129 al. 1 CC, 261 al. 1 CPC (CH)